SARS-CoV-2 rapid serological tests for field-based healthcare workers in homeless communities: A mixed-methods exploratory analysis - Emilie Mosnier; Olivia Nevissas; Sandrine Loubière; Marine Mosnier; Thomas Bosetti; Julie Bottero; Perrine Roux; Elisabetta Monfardini; Aurélie Tinland (Elsevier, 2021)
Objectives: The high risk of SARS-CoV-2 transmission in homeless communities requires adapted prevention strategies for field-based healthcare workers (HCWs). Rapid serological tests (RSTs) could be an invaluable tool for HCWs to control COVID-19 transmission. This study assesses the benefits of RSTs for HCWs in Marseille, France. Study design: Mixed-methods exploratory analysis. Methods: A mixed-methods approach was used, combining quantitative and qualitative data, to prospectively analyse acceptability of RSTs, prevalence of SARS-CoV-2 antibodies and prevention behaviours in 106 HCWs from 18 non-governmental organisations (NGOs) and health or social institutions in Marseille from June 1 to July 31, 2020. For the qualitative dimension, semi-structured individual interviews were conducted with 21 HCWs from 7 of 18 NGOs and institutions. Results: Most of the 106 HCWs in the quantitative study reported better prevention measures at work than in their homes. Despite this, the majority reported that they felt unsafe at work in terms of COVID-19 infection risk. SARS-CoV-2 antibody seroprevalence among the study population was 6.1%. Only four HCWs refused to have an RST.The 21 qualitative interviews highlighted that HCWs were not afraid of RSTs or of any possible stigma associated with a positive serological status, although they were sometimes suspicious about RST validity. Downplaying their risk of infection was a coping strategy to keep both a sense of control and remain motivated at work. Conclusions: RSTs should be adopted as an additional tool in the strategy to protect both HCWs and healthcare service users. Additional follow-up of these observational findings is needed, especially with the increasing prevalence of vaccination in HCWs.